EFFECT OF ASHWAGANDHA GHRITA AND ASHWAGANDHA GRANULES ON GROWTH W.S.R. OF BIOCHEMICAL VALUES - Rakesh, Kumar Mishra (International Journal of Ayurveda and Pharma Research, 2016)
Imagination of a â€œShareeramadyam khalu dharma sadhanamâ€ is not the new slogan, but rooting to the depth of history of ancient Indian literatures. Brumhana therapy is very well documented in literary works from the antiquity by Charaka and Sushruta. The term Brumhana refers to increase in the size or bulk of the body which ultimately refers to growth. Charaka has indicated Brumhana therapy in both healthy and diseased conditions. The â€œBhashajya Ratnavaliâ€ clearly refers regarding the potency and use of â€œAswagangha Ghritâ€ for the purpose of Brumhana; especially for children. Thus an effort had been made to prove the validity of the growth (increase in bulk of Dhatus - cellular to molecular level) in paediatric practice with support of physical, haematological and biochemical evaluation and another venture was made on the unexplored topic of Ashwagandha Ghrita which is compared with Ashwagandha Granules.In this study total 111 children completed the treatment and they were randomly divided in three groups Viz. A, B & C. In Group-A, Ashwagandha Ghrita was administered in 41 children, In Group-B, Ashwagandha Granule was administered in 36 children, and in Group- C Placebo capsules was administered in 34 children, whereas better percentage of improvement was seen in Group A.